Assessment of Physicochemical Properties of Laundry Soaps Prepared From Mango and Avocado Seed Oils and Their Blends: Giving Attention to Fruit Left Overs - A. Legesse; M. Mengisteab (Journal of Applied Sciences and Environmental Management, 2024)
It is a common practice to use oils extracted from fruits seeds for soap making. The oils are non-edible to avoid food competition. The objective of the present study was to assess the possibility of preparing a soap of acceptable quality from oils extracted from seeds of Avocado and Mango. The ground Avocado and Mango seeds were subjected to Soxhlet extraction technique using n-hexane as an organic solvent. The oil yield of 2.43% and 1.32% were obtained for Avocado seed and Mango seed samples, respectively. The analyses of the physicochemical properties such as saponification value, acid value, percent free fatty acid, and relative density were found to be 25.245 and 84.15, 30.86 and 30.85, 6.26 and 6.26, 0.87 and 0.83, respectively, and the data were in favor of utilization of the oils in soap making. Moreover, the blends of extracted Avocado and Mango seed oils in a 1:1, 3:1 and 1:3 ratios (by mass) revealed Saponification values of 151.47, 162.69, 214.62, respectively; total fatty matter contents of 59±1.41, 63 ± 1.41, 67±1.41, respectively; total alkali contents of 1.44 ± 0.03, 1.715 ± 0.08, 1.77 ± 0.13, respectively. The pH values of soaps prepared from the two oils and their blends were found to be in the range of 9.6-10.15. The data are comparable to commercial soaps and also suggest that the prepared soaps from the extracted oils can be used for cleaning purpose without any harm on human skin.